EVALUATION ON THE IMPLEMENTATION OF CUTTING AND DEPOSITION OF INCOME TAX ARTICLE 21 IN EMPLOYEES OF PT. DAYA MITRA SARANA - Gembira Siregar; Banggas Sitorus; Rutman Lumbantoruan (Fundamental Management Journal, 2021)
Taxes are useful as the main source of revenue from the State Budget and are used to finance all State interests. Therefore, improving services and people's welfare is the final goal of the imposition of taxes. One of the things that the government is trying to attract the public's trust to pay taxes is by implementing a self-assessment system. Therefore the authors want to know the implementation of withholding and depositing income tax article 21 on employees of PT. Daya Mitra Sarana and to find out whether PT. Daya Mitra Sarana is compliant and compliant with the regulations. The method used in this writing is the interview method and literature method. The conclusions that the authors can get as a result of the Job Training Report and the discussion that has been done at PT. Daya Mitra Sarana regarding the Evaluation of the Implementation of Withholding and Depositing Income Tax (PPh) Article 21 for employees, namely the calculation / Withholding and deposit of income tax (PPh) 21 at PT. Daya Mitra Sarana is done every month correctly and never too late and is in accordance with Law No. 36 of 2008 concerning income tax and the Director General of Taxes Regulation No. PER-16 / PJ / 2016. Keyword : Income, tax (PPh) 21